GPS-Daten zur Detektion von muskulärer Ermüdung in den Sportspielen - Brochhagen, J.; Ackermann, N.; Heinrich, L.; Hoppe, M. W. (Leipziger Sportwissenschaftliche Beiträge, 2022)
Summary: The aim of the study was to examine, whether Global Positioning System based data (speed, acceleration and metabolic power) can be used to detect muscular fatigue in team sports. 16 team sport players (23 ± 2 years) completed a repeated change of direction sprint protocol to induce muscular fatigue. Furthermore, a Counter Movement Jump was conducted before and after the sprint protocol, as a standardized muscular function test to objectivate fatigue. The sprint protocol induced muscular fatigue and this could most clearly be detected by changes in the metabolic power, as shown by percentual differences, significances and effect sizes.